Antimicrobial peptide hybrid fluorescent protein based sensor array discriminate ten most frequent clinic isolates - Fan, Xiaobo; Han, Jinsong; Wink, Michael (Biochimica et biophysica acta. General subjects, 2019)
Antimicrobial peptides killed bacteria through intercalating into the bacterial membrane. Their antimicrobial efficiencies varied in bacterial species and were affected by ion strength in the culture medium. A recombinant IGP protein consisted of an antimicrobial peptide, Ib-AMP4 fused with the Green Fluorescent Protein was expressed from E. coli cells and was found to maintain the antimicrobial activity. We demonstrated the interaction between the lipid membranes with IGP by quartz crystal microbalance with dissipation and tried to elucidate the effect of calcium ions by lipopolysaccharide monolayer surface isotherm assays. Ten most frequent clinic isolates were subjected to IGP incubation in buffers containing different calcium ion concentrations. The yielded fluorescent intensities ranging from several thousand to several million, differed greatly between species allowing big coefficient of variances that rendered this method a superior reproducibility and resolution. The classification and data treatment were performed by pattern identification with linear discriminant analysis. Seventy-nine isolates of the 10 most frequent clinic species were classified in the blind test with accuracy >70% by a single measurement and with a 100% accuracy by combined measurements for each species. In conclusion, the concept is based on a solid fact that antimicrobial proteins inhibit bacterial growth at a constant minimal inhibitory concentration through intercalating into the biomembrane. The developed method has a good resolution and high-faulty tolerance rate in discriminating bacteria.